Raiders! - Benton, Lynne; Morris, Tony (England, Heinemann - Pearson educational publishers, 1998)
When Jack falls asleep in a tent, he wakes up in Anglo-Saxon times$1 (Bjust as Viking raiders are about to attack! Can he warn the villagers in time and help save his family? A thrilling time-slip adventure full of danger and bravery.s
Keywords: English fiction